Synthesis of Mo2C and W2C Nanoparticle Electrocatalysts for the Efficient Hydrogen Evolution Reaction in Alkali and Acid Electrolytes - Hussain, Sajjad; Vikraman, Dhanasekaran; Feroze, Asad; Song, Wooseok; An, Ki-Seok; Kim, Hyun-Seok; Chun, Seung-Hyun; Jung, Jongwan (Frontiers in Chemistry, 2019)
The development of low-cost, high efficiency, and sustainable hydrogen production electrocatalyst based on non-precious-metal remains a great challenge. Herein, we demonstrate a facile and cost effective chemical reduction method to synthesize the molybdenum carbide (Mo2C) and tungsten carbide (W2C) nanoparticles as efficient electrocatalysts in the alkali and acid electrolytes for hydrogen evolution reactions (HER). Mo2C exhibits an outstanding catalytic activity with a small overpotential of -134 mV in acid media and -116 mV in alkaline media, while W2C nanoparticles requires an overpotential of -173 mV in acid media and -130 mV in alkaline solution to achieve a current density of 10 mA cm-2. The observed results proved the capablilty of high and low pH active electrocatalysts of Mo2C and W2C nanoparticles to be an inevitable system for hydrogen production through the HER water electrolysis.